A Commentary on “Cervical Rotation-Traction Manipulation for Cervical Radiculopathy: A Systematic Review and Meta-Analysis of Randomized Control Trials” [Letter] - Mou Y; Liu Z; Ma R (Journal of Pain Research)
Yika Mou,1 Zhen Liu,1 Ruijie Ma1,2 1The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 2Department of Acupuncture and Moxibustion, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of ChinaCorrespondence: Ruijie Ma, The Third Clinical Medical College of Zhejiang Chinese Medical University, No. 548, Binwen Road, Hangzhou, Zhejiang, 310053, People’s Republic of China, Email maria7878@sina.com